2019
DOI: 10.20944/preprints201908.0301.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of Fiber Content on Shear Capacity of Steel Fiber Reinforced Concrete Beams

Abstract: For shear-critical structural elements where the use of stirrups is not desirable, such as slabs or beams with reinforcement congestion, steel fibers can be used as shear reinforcement. The contribution of the steel fibers to the shear capacity lies in the action of the steel fibers bridging the shear crack, which increases the shear capacity and prevents a brittle failure mode. This study evaluates the effect of the amount of fibers in a concrete mix on the shear capacity of steel fiber reinforced concrete be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The fiber factor F [125][126][127][128] takes into account the geometry of the fibers (length and diameter) [53,129], the amount of fibers (fiber volume fraction) [69,70,130], and the bond properties of the fibers, which depends on the fiber type [4,[131][132][133]. A challenge here was to ascribe bond properties to the less common fiber types that were encountered in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The fiber factor F [125][126][127][128] takes into account the geometry of the fibers (length and diameter) [53,129], the amount of fibers (fiber volume fraction) [69,70,130], and the bond properties of the fibers, which depends on the fiber type [4,[131][132][133]. A challenge here was to ascribe bond properties to the less common fiber types that were encountered in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of the models used in the study [66] One of the studies that dealt with the type of failure and shear behavior of reinforced concrete beams was presented by researchers Torres and Eva [68] using (10) concrete beams without stirrups reinforcement and dimensions (100 * 120 * 970mm) steel fibers were used in proportions (0.0-0.3-0.6-0.9-1.2% ) with the specifications of length (60mm), diameter (0.75mm), tensile stress (1225MPa), and after examining the models, the researchers concluded that the percentage of steel fibers (1.2%) of the concrete volume can compensate for the use of the minimum shear reinforcing and the type of failure was for the beams For all ratios, shear failure, except for the beams that used (1.2%) steel fibers, the type of failure was Flexure Failure, and the following figure shows the models upon inspection…”
Section: Figure (00)mentioning
confidence: 99%
“…Since FRC has high toughness and resistance to impact, its use may be beneficial in the precast industry due to reduced susceptibility to damage during transport and handling. Furthermore, the use of steel fibers has been shown to result in higher resistance to shear failure of reinforced concrete beams, thereby reducing the need for stirrups [ 20 , 21 , 22 ]. In compressed elements, conventional reinforcement (i.e., rebars) may be replaced by fiber reinforcement [ 23 ].…”
Section: Introductionmentioning
confidence: 99%